Perjodohan Sebagai Upaya Mengurangi Tingkat Perceraian Dalam Pernikahan (Studi Kasus Kecamatan Sangatta Utara) - Ferdiansyah, Ferdiansyah; Hartono, Hartono; Siti Munfiatik (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Marriage is a common thing in society but there are several phenomena such as LGBT, career women, pregnancy outside marriage, high dowry and others. This has an impact on society because the number of marriages decreases, while the number of divorces increases every year. This research aims to understand the role of arranged marriage as an effort to reduce the divorce rate in marriage. This research uses a descriptive method with a qualitative approach used to understand and explain social phenomena in depth and detail. The results showed that arranged marriage can play a role in reducing the divorce rate in marriage because of the factors that arise due to arranged marriage such as value compatibility, background, strong commitment, strong social support, more realistic expectations. However, the success of arranged marriage also depends on the readiness factor of the couple, good communication before marriage. Therefore, arranged marriage is not the only, but can be one of the effective approaches in creating a stable and harmonious marriage.